The Impact of COVID-19 on Challenges and Protection Practices of Migrant Workers' Rights - Anom Wahyu Asmorojati; Muhammad Nur; Indah Kusuma Dewi; Hezlina Hashim (BESTUUR, 2022)
Indonesia has agreed to the ASEAN Consensus on the Promotion and Protection of the Rights of Migrant Workers. However, many cases have proved the vulnerability of the legal protection for Indonesian migrant workers in Malaysia. In other words, the consensus has not protected the workers. Therefore, this research was conducted to analyze considerations for the regulations designed to protect post-consensus migrant workers. The objective comprised three aspects: analysis of the legislation after consensus, the draft policy that realizes the consensus, and the enforcement based on the draft formulated to safeguard the rights of migrant workers—a normative juridical method used in this research. The results showed that the consensus is a soft law that does not have a binding effect and sanction, causing it vulnerable to a violation, especially among undocumented migrant workers.  Therefore, the research recommends bureaucracy reform to reduce the administrative costs for the migrant workers, allowing them to have better legal protection.